2019
DOI: 10.1155/2019/4615745
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Potential Therapeutic Use of Lycium Barbarum Polysaccharides in Disease

Abstract: Objective. To evaluate the effect of Lycium barbarum polysaccharides in the treatment and/or prevention of diseases of different etiologies and systems. Methods. We performed an Entrez PubMed literature search using keywords “lycium”, “barbarum”, “polysaccharides”, “anti-fibrotic”, “anti-apoptotic”, “anti-oxidizing”, “anti-aging”, “neuroprotection”, “metabolism”, “diabetes”, “hyperlipidemia”, “neuroprotection”, and “immunomodulation” on the 14th of August 2018, resulting in 207 papers, of which 20 were chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 43 publications
2
40
0
2
Order By: Relevance
“…LBPs contains 6 monosaccharides, including xylose, rhamnose, mannose, galactose, arabinose and glucose, which exert multiple therapeutic functions such as anti-cancer, antiinflammation, anti-fibrosis and antioxidant [21]. Noteworthily, LBPs have been evidenced to have neuro protective efficacy and are beneficial in cardiovascular and cerebrovascular diseases [21]. It is reported LBPs can induce cell autophagy to protect against peripheral neuropathy in streptozotocininduced diabetic rats [22].…”
Section: Discussionmentioning
confidence: 99%
“…LBPs contains 6 monosaccharides, including xylose, rhamnose, mannose, galactose, arabinose and glucose, which exert multiple therapeutic functions such as anti-cancer, antiinflammation, anti-fibrosis and antioxidant [21]. Noteworthily, LBPs have been evidenced to have neuro protective efficacy and are beneficial in cardiovascular and cerebrovascular diseases [21]. It is reported LBPs can induce cell autophagy to protect against peripheral neuropathy in streptozotocininduced diabetic rats [22].…”
Section: Discussionmentioning
confidence: 99%
“…Chien et al investigated the potential therapeutic effects of LBP extract in dry eye disease. Rats treated with oral LBP extract had a significantly higher Schirmer's test score and tear break-up time with reduced fluorescein staining compared to other groups in a dose-dependent manner [27,28]. Du et al assessed the effect of LBP extract in UV-B damaged corneal epithelial cells and found that LBP prevents apoptosis of injured corneal epithelial cells via inhibition of the JNK-Bax-caspase 3 pathway [17].…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro model demonstrates the anti-fibrotic potential of LBP extract. One of the major concerns with the use of LBP has been a lack of availability of standardized research-grade LBP formulation [27]. Previous studies have resourced LBP from large-scale nutraceutical companies which offer a large range of LBP purity and sourcing [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, potential pharmacological interference with conventional drugs may be common and remains poorly investigated. For instance, high quality evidence about the clinical efficacy of Pannax ginseng, Lycium barbarum and Cinnamon, the three most extensively exported Chinese herbs, is practically non-existent [89][90][91]. Moreover, a comprehensive report of Cochrane reviews on Chinese herbal medicines (CHM) suggested that only 16% of all included primary studies use adequate sequence generation.…”
Section: Tcm Therapeutics-forgotten Treasure or Pandora's Box?mentioning
confidence: 99%